Case report: A novel mutation of the CAPN3 gene in a Chinese family with limb-girdle muscular dystrophy type 2A - Feng, Wanjun; Cao, Yanyan; Ren, Ruolin; Yang, Xiaohui; Cao, Chunyan; Jiang, Hongwei; Du, Ganqin (Frontiers in Genetics, 2024)
Limb girdle muscular dystrophy type 2A (LGMD R1 Calpain 3-Related,LGMD2A/R1), an autosomal recessive disorder, is characterized by progressive muscle weakness with a prominent presentation in the proximal limb girdle muscles.LGMD2A/R1 which caused by variants in calcium-activated neutral proteinase 3 (CAPN3) is the most common. The present study aimed at identifying the clinically significant variants in a Chinese family with LGMD2A/R1 and exploring the genotypephenotype correlations. Clinical symptom, laboratory findings and physical examination were obtained. Genomic DNA was extracted from the peripheral blood samples of this family. Whole-exome sequencing (WES) and sanger sequencing were used to explore and validate the pathogenic genes. In this study, proband and his sister who had two identical mutations in the CAPN3 gene sequence exhibited diverse clinical features including disease onset and progression. The mutation c.2120 A>G (p. D707G) is pathogenic which has been reported in the Human Gene Mutation Database (HGMD) and ClinVar database. c.1783-72 C>G may be a novel pathogenic mutation ofLGMD2A/R1 based on the ACMG (the American College of Medical Genetics guidelines), which widens the gene variant pool in CAPN3, improve diagnosis and genetic counselling.